THE IMPLEMENTATION OF EXPERIENCE TEXT RELATIONSHIP (ETR) METHOD FOR TEACHING READING COMPREHENSION IN NARRATIVE TEXT - Yanti Susanti (Journal of English Education Program (JEEP), 2016)
This study reports on the implementation of Experience Text Relationship (ETR) method in teaching reading comprehension in narrative text to junior high school students. The aims of this study were to investigate the teacher ways of using Experience Text Relationship (ETR) method in teaching reading comprehension in narrative text and to examine students’ responses towards the implementation of Experience Text Relationship (ETR) method in learning reading comprehension in narrative text. Eighth grade students of SMP N 7 Ciamis were participated in this study. Moreover, this study employed case study as the research design. The result revealed that the implementation of Experience Text Relationship (ETR) method for teaching reading comprehension in narrative text help the students to comprehending the narrative text. In other words, the implementation of Experience Text Relationship (ETR) method has a significant effect in improving students’ reading comprehension in narrative text on students reading activities. Besides, students responded positively towards the implementation of Experience Text Relationship (ETR) method in their learning. They felt interested and easy to comprehend the text especially narrative text.Keywords: Reading Comprehension, Experience-Text Relationship (ETR) Method, Narrative Text